Susceptibility of the predator Euborellia annulipes (Dermaptera: Anisolabididae) to mycoinsecticides - QUEIROZ DE OLIVEIRA, FLÁVIA; DE LUNA BATISTA, JACINTO; MALAQUIAS, JOSÉ BRUNO; DE BRITO, CARLOS HENRIQUE; PEREIRA DOS SANTOS, EMMERSON (Revista Colombiana de Entomología, 2011)
To evaluate the influence of Beauveria bassiana (Balsamo) Vuill and Metarhizium anisopliae (Metsch) Sorok on the survival of the predator Euborellia annulipes Lucas (Dermaptera: Anisolabididae) were used product concentrations 5.00x109; 7.50x109; 10.00x109; 12.50x109 conidia/L from isolates of B. bassiana and M. anisopliae which were obtained, respectively, through products Boveril® and Metarril® and control (0.0 conidia/L). High rates of hatching nymphs of E. annulipes have been recorded in clutches that received applications of M. anisopliae. Moreover, B. bassiana has affected negatively the hatching rate of nymphs of E. annulipes. A slightly harmful effect has been observed in all concentrations of conidia B. bassiana in clutches of E. annulipes. The survival was 100% in all tested concentrations of M. anisopliae in females of E. annulipes. The females which received topical application of B. bassiana have shown a survival rate ranging from 80.30 (12.50x109 conidia) to 100% (5.00x109 conidia). In males of E. annulipes, the survival rate in insects treated with B. bassiana ranged from 95.00 (12.50x109 conidia) to 100% (5.00x109 conidia), while with M. anisopliae applications this rate was 96.02 (12.50x109 conidia) to 100% (5.00x109 conidia). The entomopathogenic fungi B. bassiana and M. anisopliae did not affect the mortality of nymphs and adults of E. annulipes. However, careful measures should be adopted in applications of B. bassiana directly into clutches of E. annulipes.